2016
DOI: 10.5604/15093492.1205022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in Diagnosis of Myofascial Pain Syndrome and Reliability of Novel Ultrasonic Indexes of Upper Trapezius Muscle

Abstract: SUMMARYBackground. Myofascial pain syndrome (MPS) is a common non-articular musculoskeletal disorder. It is characterized by local and referred pain due to the presence of myofascial trigger points (MTrPs). MTrPs most commonly involve the upper trapezius muscle and can be visualized using ultrasound imaging. This study was designed to determine the inter-rater reliability of some new ultrasonographic indices of the upper trapezius muscle and the sensitivity and specificity of 2D ultrasound imaging in the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…78 Although ultrasound and other tests have been advocated to identify trigger points and myofascial neck pain, physical examination remains the reference standard. 79 One meta-analysis performed in people with chronic neck pain found that the point prevalence of active trigger points ranged from 14.8% in the right levator scapula to 38.5% in the right upper trapezius. 80 The treatment of myofascial pain should be multimodal and should include correcting underlying structural and postural imbalances, physical therapy (for example, massage and range of motion exercises), drugs, and psychotherapy (including cognitive behavioral therapy and biofeedback).…”
Section: Myofascial Painmentioning
confidence: 99%
“…78 Although ultrasound and other tests have been advocated to identify trigger points and myofascial neck pain, physical examination remains the reference standard. 79 One meta-analysis performed in people with chronic neck pain found that the point prevalence of active trigger points ranged from 14.8% in the right levator scapula to 38.5% in the right upper trapezius. 80 The treatment of myofascial pain should be multimodal and should include correcting underlying structural and postural imbalances, physical therapy (for example, massage and range of motion exercises), drugs, and psychotherapy (including cognitive behavioral therapy and biofeedback).…”
Section: Myofascial Painmentioning
confidence: 99%
“…The included studies (see Table 1) are cross-sectional clinical diagnostic research conducted in the United States, 60 Iran, 61 South Korea, 62 Egypt, 61 Malaysia, 49 and Australia. 63 One study was published in 1999, 63 and the remaining studies were published from 2011 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…MTrPs were defined as 0.05 to 0.5 cm 2 heterogeneous, 60,61 hypoechoic clusters 1 or single nodules. 1,60,61 Two exceptions were Lewis and Tehan, 63 who described MTrPs as 5 mm hyperechoic nodules; and Hafiza et al, 49 who described the MTrPs as the peak of a curved muscle structure. The twitch response was defined as a momentary contraction.…”
Section: Resultsmentioning
confidence: 99%
“…[1,7]. Taheri et al describe that the musculoskeletal ultrasonography has higher sensitivity in diagnosing hypoechoeic myofascial trigger points and appears to be useful in diagnosing piriformis myofascial pain syndrome, however its reliability should be tested in a longitudinal study with large number study participants [15]. So in terms of confirmed diagnostic test for PS we are yet to have the most appropriate one.…”
Section: What Are the Common Diagnostic Features Of Ps?mentioning
confidence: 99%